DYSGERMINOMA IN PREGNANCY: A CASE REPORT - Mihaljević, Olga (Medical Research, 2023)
Introduction: Malignant germ cell tumors (MGCTs), as a subtype of rare non-epithelial ovarian cancers (NOEC), are most commonly found in pregnancy. Out of all MGCTs 38% are dysgerminoma. Since the rarity of this entities, the aim of this paper is to show a rare case of ovarian dysgerminoma presented in pregnancy and its influence on course and outcome of the pregnancy.Patient Review: Patient aged 26 years, gravida 2, para 1, with one vaginal delivery five years ago, was admitted to Clinic for Gynecology and obstetrics in term pregnancy because of uterine contractions accompanied by left thigh pain and tingling sensation in left leg. Solid hypoechogenic mass with regular border and 125x90 mm in diameter adjacent to the left side of the uterus was seen by ultrasound, without free fluid in pelvic cavity. Since regular uterine contractions started, the decision was made to terminate pregnancy by Caesarean section (CS) because of tumor previa. Histopathological examination confirmed ovarian dysgerminoma, but after staging operation which was performed two months after CS, following imaging diagnostics, ovarian dysgerminoma was confirmed with FIGO stage IA, meaning that patient's specific oncological treatment was finished.Conclusion: Diagnosis of ovarian dysgerminoma is in general challenging since up to 50% are asymptomatic or symptoms are non-specific. The management of ovarian cancer in pregnancy should be multidisciplinary and individualized in the best interest for mother and the fetus. The overall five-year survival rate for ovarian dysgerminoma is favorable in more than 90%. Women diagnosed with dysgerminoma in pregnancy are young and in general have good feto-maternal outcome.
Keywords: Ovarian dysgerminoma, feto-maternal outcome, dysgerminoma in pregnancy, ovarian cancer, cancer in pregnancy